Enterprises Using Radio Frequency Identification in European Union: Current Outlook (2009-2014) - Jovana Zoroja; Igor Klopotan; Vanja Šimičević (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Implementation and usage of the latest inventions in information technology provides enterprises better position on the global market. Radio Frequency Identification (RFID) presents the innovative information technology that can change and improve many of the enterprises collaboration operations and support decision making process. The best results of RFID usage are achieved in the supply chain systems, but RFID can be applied in the fields of medicine, finance, logistics and trade. Goal of this paper is to evaluate trends and purposes of RFID usage among enterprises in European Union. We also analyse usage of RFID among Enterprises in European Union according to the industry. Future research will focus on application of RFID among enterprises worldwide and to examine are there any differences in RFID usage among developed and developing countries.
Keywords: C10; C38; N7; 330; Radio Frequency Identification; Technology; Enterprises; European Union Countries